High-performance 4.5-micron electrolytic copper foil additive and application thereof

By using cerium-polyacrylamide composite microspheres in 4.5 micron electrolytic copper foil to cooperate with other additives, the problems of low tensile strength, insufficient elongation and poor surface quality of the electrolytic copper foil are solved, and the production of high-performance electrolytic copper foil is achieved to meet the high-performance needs of power lithium batteries.

CN119530902APending Publication Date: 2025-02-28ANHUI HUIRU TECH CO LTD

Patent Information

Application Number
CN202411756564.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing 4.5-micron electrolytic copper foil has problems such as low tensile strength, insufficient elongation and poor surface quality in production and use, which cannot meet the demand for high-performance electrolytic copper foils of power lithium batteries.

Method used

The composite microspheres were prepared by in-situ polymerization method using cerium-polyacrylamide composite microspheres as additives, and used in combination with sulfur-containing brightener, leveling agent and wetting agent to form a high-performance 4.5 micron electrolytic copper foil additive.

Benefits of technology

The tensile strength and elongation of 4.5 micron electrolytic copper foil were significantly improved, reaching 400-500MPa and above 6%, respectively, improving the surface quality, enhancing the mechanical properties and production reliability of the copper foil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530902A_ABST
    Figure CN119530902A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance 4.5-micron electrolytic copper foil additive and application thereof, and belongs to the technical field of electrolytic copper foils. The additive comprises cerium-polyacrylamide composite microspheres, a sulfur-containing brightener, a leveling agent, a wetting agent and the like, the cerium-polyacrylamide composite microspheres are inorganic-organic composite materials formed by rare earth element cerium and polyacrylamide, and the cerium-polyacrylamide composite microspheres are prepared through an in-situ polymerization method. Monomer acrylamide of polyacrylamide grows around cerium ions in situ, so that the cerium ions are fixed around a polymer chain, and a relatively stable dispersion system is formed. The 4.5-micron electrolytic copper foil prepared by adopting the additive has good surface quality and relatively high tensile strength and ductility. Particularly, the tensile strength and the elongation performance can reach 400-500 MPa and 6% or above respectively, and the production and application reliability of the 4.5-micron copper foil is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytic copper foil, and in particular, relates to a high-performance 4.5-micron electrolytic copper foil additive and application thereof. Background Art

[0002] The precise use of additives in the production process of electrolytic copper foil, especially thin copper foil used in lithium-ion batteries, is crucial. Additives, such as brighteners, wetting agents, levelers and inhibitors, each play a key role in improving the surface finish of copper foil, controlling the stability of additives, ensuring surface flatness, and regulating the copper deposition rate. For ultra-thin copper foil (below 6μm), the selection and formulation complexity of these additives are significantly improved. Since ultra-thin copper foil is prone to defects such as uneven thickness, pinholes and cracks during production, levelers and inhibitors are more needed to finely control the uniform growth of copper crystals and prevent local excessive deposition, while optimizing the brightener formula to ensure surface finish and material strength. In contrast, thin copper foil and ultra-thin copper foil (6-18μm) are relatively less dependent on additives in production, and the tolerance rate in the deposition process is increased due to increased thickness. Therefore, the production of ultra-thin copper foil places higher requirements on the precise formulation and regulation of additives to achieve high performance and high stability of copper foil.

[0003] In recent years, the rapid penetration of new energy vehicles has greatly promoted the rapid development of lithium battery related industries. With the increasing speed of technological iteration, the trend of lightweight power lithium batteries is gradually becoming prominent, developing towards smaller, lighter and higher energy density. At the same time, it also puts forward requirements for thinning, high tensile strength and high elongation for electrolytic copper foil as the negative electrode current collector of lithium batteries. At present, the demand for lithium battery copper foil in the power battery market has transitioned from 8 microns to 6 microns. Leading companies have begun to switch to 4.5-micron products, and the proportion of shipments is gradually increasing. However, as the thickness of copper foil continues to decrease, internal structural defects, impurities, etc. are more likely to affect its mechanical properties. The 4.5-micron copper foil manufactured by ordinary double-sided photoelectrolytic copper foil additives has many microstructural defects, low tensile strength, poor surface quality and other problems, which cannot meet its extremely demanding reliability requirements in production and use. Therefore, it is necessary to study the additive formula for 4.5-micron electrolytic copper foil with good surface quality, high tensile strength and high elongation performance.

[0004] The Chinese invention patent with publication number CN112760682A discloses an electrolyte for improving pinholes in 4.5 micron lithium ion electrolytic copper foil, including adding an additive for improving pinholes in 4.5 micron lithium ion electrolytic copper foil to the electrolyte. The additive for improving pinholes in 4.5 micron lithium ion electrolytic copper foil includes: 1-10 ppm disulfide-containing additive, 0.1-2 ppm DPS or ZPS, 10-50 ppm collagen or gelatin, 0.1-2 ppm potassium benzenesulfonate, sodium benzenesulfonate, at least one of the above; the electrolyte copper dissolution parameter is 80-110 g / L Cu 2+ , 90~110g / L H2SO4, 10~50mg / L Cl - The electrolyte can greatly reduce the occurrence of pinholes in 4.5-micron copper foil, but there is no data to support its effect on the tensile strength and elongation of 4.5-micron copper foil. For another example, the Chinese invention patent with publication number CN110644021A discloses a 4.5 micron electrolytic copper foil for lithium ion batteries, a preparation method and an additive, wherein the additive is made of raw materials with the following proportions: 2.5-3 g / L polyquaternium-10, 3.5-4 g / L polyquaternium-7, 2.5-3 g / L polyquaternium-51, 2-2.5 g / L sodium polydisulfide propane sulfonate, 0.75-1.25 g / L sodium alcoholthiopropane sulfonate, ≤0.5 g / L gelatin, ≤0.5 g / L alkaline saffron dye, ≤0.5 g / L N-butylthiourea, 0.75-1.25 g / L sodium mercaptoimidazole benzene sulfonate and ≤0.75 g / L polyethylene glycol formal. The additive formula can make the 4.5 micron electrolytic copper foil have higher room temperature tensile strength and elongation while ensuring good surface quality, but still within the range of ordinary tensile strength.

[0005] Another example is the Chinese invention patent with publication number CN113652718A, which discloses a preparation method, product and application of a 3-micron electrolytic copper foil additive. Its raw material components include sodium alkylphenol polyoxyethylene sulfonate, cerium sulfate, octylphenol polyoxyethylene ether, sodium phenyl disulfide propane sulfonate, sodium dodecyl sulfate, sodium naphthalene disulfonate, sodium 3-(benzothiazole-2-mercapto) propane sulfonate, and hydroxyethyl cellulose. The rare earth additive in this invention can improve the performance of the plating solution, improve the cathode current efficiency, make the coating grains small and dense, and make the copper foil surface bright and delicate, which can improve the welding effect and antioxidant ability. The ultra-thin electrolytic copper foil produced has good conductivity, smooth surface grains, low profile, and good physical parameters, such as a unit area weight of 28±2g / mm 2 , Room temperature tensile strength ≥ 27Kg / mm 2 , room temperature elongation ≥ 2.5%, high temperature tensile strength ≥ 20Kg / mm 2, high temperature elongation ≥ 3%, surface roughness Ra ≤ 0.25 μm, Rz ≤ 2.5 μm. However, this invention has many additives and is complicated to apply. The tensile strength of the 3 μm ultra-thin electrolytic copper foil is low (< 300Mpa), which is difficult to be actually applied in large-scale production. Summary of the invention

[0006] The purpose of the present invention is to provide a high-performance 4.5 micron electrolytic copper foil additive and its application. The 4.5 micron electrolytic copper foil prepared by using the additive has good surface quality, high tensile strength and elongation. In particular, the tensile strength and elongation performance can reach 400-500 MPa and more than 6%, respectively, which greatly improves the production and application reliability of the 4.5 micron copper foil.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A high-performance 4.5 micron electrolytic copper foil additive, comprising the following components in parts by weight:

[0009] 32-65 parts of cerium-polyacrylamide composite microspheres

[0010] Sulfur-containing brightener 2800-2870 parts

[0011] Leveling agent 3360~3500 parts

[0012] Wetting agent 20-26 parts

[0013] 430,000 to 440,000 parts of deionized water.

[0014] The cerium-polyacrylamide composite microspheres are an inorganic-organic composite material formed by rare earth element cerium and polyacrylamide. The material uses an in-situ polymerization method to make the monomer acrylamide of polyacrylamide grow in-situ around the cerium ions, so that the cerium ions are "fixed" around the polymer chain to form a relatively stable dispersion system, which solves the problem that cerium ions are prone to agglomeration in the solution system. The preparation method of the cerium-polyacrylamide composite microspheres is as follows:

[0015] (S1) Raw material preparation: select cerium salt, which is one or more of cerium nitrate, ammonium cerium nitrate, cerium sulfate, and cerium chloride, dissolve the cerium salt in deionized water to prepare a cerium ion solution with a concentration of 0.1-1 mol / L. During the dissolution process, use a magnetic stirrer to stir at room temperature for 30-60 minutes to ensure that the cerium salt is completely dissolved to obtain a uniform cerium ion solution; weigh acrylamide monomer and dry it in a vacuum drying oven at 40-50°C for 2-3 hours before use to remove moisture. Prepare an initiator, a cross-linking agent, and a surfactant, wherein the initiator is ammonium persulfate or potassium persulfate, the cross-linking agent is N,N-methylenebisacrylamide, and the surfactant is sodium dodecyl sulfate or sodium dodecylbenzene sulfonate.

[0016] (S2) Monomer dissolution: Slowly add the dried acrylamide monomer to the cerium ion solution to make the concentration of acrylamide monomer 1-5 mol / L. Use a mechanical stirrer at a speed of 300-500 rpm to stir for 20-30 minutes until the acrylamide monomer is completely dissolved in the cerium ion solution to form a mixed solution.

[0017] (S3) Adding auxiliary agents: Initiator, crosslinker and surfactant are added to the mixed solution in sequence. The amount of initiator added is 0.5%-2% of the mass of acrylamide monomer, the amount of crosslinker added is 0.05%-0.5% of the mass of acrylamide monomer, and the amount of surfactant added is 2%-4% of the total mass of the reaction system. After each auxiliary agent is added, stir at a speed of 300-500 rpm for 10-15 minutes to ensure that the auxiliary agent is evenly dispersed in the solution.

[0018] (S4) In-situ polymerization: The prepared reaction system is transferred to a reactor equipped with a temperature control system and a stirring device, the temperature is raised to 50-70°C, and the reaction is continued with stirring at a speed of 200-400 rpm for 3-6 hours. During this process, the acrylamide monomer undergoes an in-situ polymerization reaction in the presence of cerium ions to form microspheres of polyacrylamide encapsulating cerium ions.

[0019] (S5) Product post-treatment: After the reaction is completed, the product in the reactor is cooled to room temperature, and then the product is transferred to a centrifuge tube, centrifuged at a speed of 3000-5000rpm for 10-20 minutes in a centrifuge, so that the microspheres are precipitated at the bottom of the centrifuge tube, the supernatant is poured out, and the microspheres are collected. Then, the collected microspheres are washed with deionized water for 3-5 times. During each washing, the microspheres are redispersed in deionized water, and then centrifuged at a speed of 3000-5000rpm for 10-20 minutes in a centrifuge, and the supernatant is poured out to remove unreacted substances and impurities. Finally, the washed microspheres are transferred to a vacuum drying oven and dried for 12-24 hours at a temperature of 50-60°C and a vacuum degree of 0.05-0.1MPa to obtain the cerium-polyacrylamide composite microspheres.

[0020] The cerium-polyacrylamide composite microspheres are mainly used to improve the electrodeposition efficiency, refine the grains, and improve the mechanical strength of the copper foil in the preparation process of the electrolytic copper foil. This is because an appropriate amount of cerium can improve the cathode polarization, effectively improve the current efficiency, and easily adsorb on the crystal growth active point to inhibit the grain growth, so that the copper foil grains are refined. After the grains are refined, the grain boundaries increase, and the grain boundaries can hinder the movement of dislocations, so that the material needs a greater external force to make the dislocations slip when it is stressed, thereby improving the tensile strength of the copper foil. After forming composite microspheres with polyacrylamide, the cerium ions can be more evenly dispersed in the electrolyte, providing more sites for the action of the cerium ions, further enhancing the effect of this grain refinement, and further improving the tensile properties of the copper foil. In addition, when the cerium ions are encapsulated in the polyacrylamide microspheres, they are slowly released during the electrodeposition process or a higher concentration of cerium ions is formed locally, thereby enhancing the effect of this grain refinement.

[0021] The sulfur-containing brightener is at least one of sodium thiopropane sulfonate (HP), sodium polydisulfide propane sulfonate (SPS), sodium dimethylformamide sulfonate (TPS), and sodium 3-mercapto-1-propane sulfonate (MPS), and mainly plays the role of refining grains and improving the surface gloss of copper foil.

[0022] The wetting agent is at least one of polyethylene glycol (molecular weight 1000), hydroxyethyl cellulose and hydroxymethyl cellulose, and its main function is to reduce the surface tension of the electrode / solution interface, promote the escape of bubbles, and prevent defects such as pinholes. At the same time, the wetting agent can be directional adsorbed on the electrode surface, improve cathode polarization, inhibit the deposition rate of copper ions, and make the coating crystal dense.

[0023] The leveling agent is at least one of tetrahydrothiazolidinethione, ethylenethiourea, gelatin and collagen, and its main function is to hinder the reduction of copper ions, reduce the peak height, slow down the contour fluctuation of the copper foil surface, and reduce the surface roughness.

[0024] According to another aspect of the present invention, the application of the additive in the electrodeposition of 4.5-micron electrolytic copper foil is provided, and the specific application process includes the following steps: the additive and the electrolyte are fully mixed and circulated at a ratio of 1:4600-5000, and the high-performance 4.5-micron electrolytic copper foil is obtained by electrodeposition.

[0025] Furthermore, the electrolyte parameters are: 85-65 g / L Cu 2+ , 95~105g / L H2SO4 and 25~35g / LCl - .

[0026] Furthermore, the temperature of the electrolyte is 50-60°C.

[0027] Furthermore, the circulation flow rate of the electrolyte is 1.2 to 2.0 L / min.

[0028] Furthermore, the current density of the electrodeposition is 23 to 30 A / dm 2 .

[0029] Furthermore, the electrodeposition time is 38 to 45 seconds.

[0030] Beneficial effects of the present invention:

[0031] (1) Give 4.5μm copper foil higher tensile strength: Cerium-polyacrylamide composite microspheres can form a synergistic effect during the electrodeposition process, which can more significantly refine the grains and improve the mechanical strength of the copper foil compared to when the two are used alone. During the electrodeposition process, cerium ions preferentially adsorb on the active sites of copper crystal growth by affecting cathode polarization, inhibiting excessive grain growth, while polyacrylamide provides a good dispersion environment and slow release for cerium ions. At the same time, it has a certain interaction with the surface of copper foil. The two work together to more effectively refine the grains of copper foil. Even when the thickness of the copper foil is 4.5μm, the tensile strength and elongation can still reach 400-500MPa and more than 6% respectively. This excellent mechanical property makes the copper foil more advantageous in subsequent processing and use. For example, in the application of lithium battery electrode materials, it can better withstand the volume change during the electrode charging and discharging process and improve the cycle life of the battery.

[0032] (2) A simpler and more stable production process: The additive formula provided by the present invention has fewer types of ingredients and good dispersibility. It can accurately and efficiently exert the role of each component, reducing the complexity and uncertainty in the production process. Due to the simple ingredients, the mutual interference problems that may exist between various complex additives, such as precipitation, chemical reactions, etc., are avoided, so that the stability of the electrolyte is improved. In the process of mixing the additives, good dispersion can be achieved by simple stirring, without the need for complex dispersing equipment and long processing processes. At the same time, this simple and stable formula can reduce the number of parameter adjustments in the production process, reduce the technical requirements for operators, improve production efficiency and consistency of product quality, and is conducive to large-scale industrial production.

[0033] (3) Good compatibility: It can be used in conjunction with most existing electrolytic copper foil additive systems. The cerium-polyacrylamide composite microsphere additive of the present invention has good compatibility in chemical properties, and it will not react chemically with common additives such as brighteners, levelers, and wetting agents. When used together with other additives, they can give full play to their respective advantages and synergistically improve the performance of the copper foil. For example, when used in conjunction with a sulfur-containing brightener, it can further enhance the mechanical properties of the copper foil while improving the surface finish of the copper foil; when used together with a leveler, it can more effectively improve the flatness of the copper foil surface and improve the overall quality of the copper foil, thereby broadening the scope of application of the additive in different electrolytic copper foil production processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The present invention will be further described below in conjunction with the accompanying drawings.

[0035] Figure 1 It is a line graph of the tensile strength of copper foil in Examples 1-4 and Comparative Examples 1-4.

[0036] Figure 2 It is a line graph of the elongation of the copper foil in Examples 1-4 and Comparative Examples 1-4.

[0037] Figure 3 It is a line graph of the surface roughness Rz of the copper foil in Examples 1-4 and Comparative Examples 1-4. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Preparation of cerium-polyacrylamide composite microspheres:

[0040] (1) Raw material preparation: Cerium nitrate was selected as cerium salt, dissolved in deionized water to prepare a cerium ion solution with a concentration of 0.5 mol / L, and magnetically stirred at room temperature for 45 minutes to completely dissolve it; acrylamide monomer was dried in a vacuum drying oven at 45° C. for 2.5 hours and then weighed; ammonium persulfate was prepared as an initiator, N,N-methylenebisacrylamide was prepared as a cross-linking agent, and sodium dodecyl sulfate was prepared as a surfactant.

[0041] (2) Monomer dissolution: The dried acrylamide monomer was slowly added to the cerium ion solution to make the monomer concentration 3 mol / L, and mechanically stirred at a speed of 400 rpm for 25 minutes until the monomer was completely dissolved to form a mixed solution.

[0042] (3) Addition of auxiliary agents: Initiator (the amount added is 1.2% of the mass of acrylamide monomer), crosslinker (the amount added is 0.3% of the mass of acrylamide monomer) and surfactant (the amount added is 3% of the total mass of the reaction system) were added to the mixed solution in sequence. After each addition, the mixture was stirred at 400 rpm for 12 minutes to ensure uniform dispersion.

[0043] (4) In-situ polymerization: The reaction system was transferred to a reactor, heated to 60° C., and stirred at 300 rpm for 4.5 hours to perform in-situ polymerization to form microspheres.

[0044] (5) Product post-treatment: After the reaction is completed, the mixture is cooled to room temperature and the product is transferred to a centrifuge tube and centrifuged at 4000 rpm for 15 minutes. The supernatant is discarded to collect the microspheres, which are then washed four times with deionized water (re-dispersed in water and centrifuged again after each washing). Finally, the washed microspheres are dried at 55°C and a vacuum degree of 0.08 MPa for 18 hours to obtain cerium-polyacrylamide composite microspheres.

[0045] Embodiment 1

[0046] (1) Take 45 parts by weight of cerium-polyacrylamide composite microspheres, 2830 parts of sulfur-containing brightener (sodium thiopropane sulfonate and sodium polydisulfide propane sulfonate mixed at a ratio of 1:1), 3420 parts of leveling agent (thiazolidinethione and gelatin mixed at a ratio of 1:1), 23 parts of wetting agent (polyethylene glycol, molecular weight 1000), and 435,000 parts of deionized water, and mix them evenly.

[0047] (2) Prepare electrolyte with the following parameters: Cu 2+ Concentration 87g / L, H2SO4 concentration 100g / L, Cl - Concentration 30g / L, electrolyte temperature 55℃.

[0048] (3) The above additives and electrolyte were fully mixed in the electrolytic cell at a ratio of 1:4700, and the circulation flow rate was set to 1.4 L / min and the electrodeposition current density was set to 26 A / dm 2 Under the above conditions, the electrodeposition time was 41s, and a high performance 4.5 micron electrolytic copper foil was obtained.

[0049] Embodiment 2

[0050] (1) By weight, 55 parts of cerium-polyacrylamide composite microspheres, 2850 parts of sulfur-containing brightener (sodium dimethylformamide sulfonate), 3450 parts of leveling agent (ethylene thiourea), 24 parts of wetting agent (hydroxyethyl cellulose), and 438,000 parts of deionized water were mixed.

[0051] (2) Prepare electrolyte, parameters are: electrolyte Cu 2+ concentration 86g / L, H2SO4 concentration 105g / L, Cl - Concentration 32g / L, temperature 58℃.

[0052] (3) After the additive and electrolyte are mixed in the electrolytic cell at a ratio of 1:4800, the circulation flow rate is set to 1.6L / min at 28A / dm 2 Under the current density condition, the electrodeposition was performed for 40 seconds to obtain the high performance 4.5 micron electrolytic copper foil.

[0053] Embodiment 3

[0054] (1) By weight, 38 parts of cerium-polyacrylamide composite microspheres, 2810 parts of sulfur-containing brightener (sodium 3-mercapto-1-propanesulfonate), 3380 parts of leveling agent (collagen), 21 parts of wetting agent (hydroxymethyl cellulose), and 432,000 parts of deionized water were mixed.

[0055] (2) Cu in electrolyte 2+ Concentration 85g / L, H2SO4 concentration 102g / L, Cl - Concentration 28g / L, temperature 52℃,

[0056] (3) After the additive and electrolyte are fully mixed in the electrolytic cell at a ratio of 1:4600, the circulation flow rate is set to 1.2L / min, 24A / dm 2 Under the current density condition, the electrodeposition was carried out for 42 seconds to obtain the high performance 4.5 micron electrolytic copper foil.

[0057] Embodiment 4

[0058] (1) By weight, 40 parts of cerium-polyacrylamide composite microspheres, 2820 parts of sulfur-containing brightener (sodium polydisulfide dipropane sulfonate), 3400 parts of leveling agent (ethylene thiourea and collagen mixed in a ratio of 2:1), 22 parts of wetting agent (hydroxyethyl cellulose and hydroxymethyl cellulose mixed in a ratio of 1:1), and 433,000 parts of deionized water were mixed uniformly.

[0059] (2) Prepare electrolyte with the following parameters: Cu 2+ Concentration 90g / L, H2SO4 concentration 96g / L, Cl - Concentration 26g / L, electrolyte temperature 53℃, circulation flow rate 35L / min.

[0060] (3) After the above-mentioned additive combination and electrolyte are fully mixed in the electrolytic cell at a ratio of 1:4650, the circulation flow rate is set to 1.3 L / min, and the electrodeposition current density is 25 A / dm 2 Under the conditions of electrodeposition time of 42s, high performance 4.5 micron electrolytic copper foil was obtained.

[0061] Comparative Example 1

[0062] (1) Take 2830 parts of sulfur-containing brightener (sodium alcoholthiopropane sulfonate and sodium polydisulfide propane sulfonate mixed in a ratio of 1:1), 3420 parts of leveler (thiazolidinethione and gelatin mixed in a ratio of 1:1), 23 parts of wetting agent (polyethylene glycol), and 435,000 parts of deionized water, and mix them evenly.

[0063] (2) Prepare electrolyte with the following parameters: Cu 2+ Concentration 87g / L, H2SO4 concentration 100g / L, Cl - Concentration 30g / L, electrolyte temperature 55℃, circulation flow rate 40L / min.

[0064] (3) The above additives and electrolyte were mixed in the electrolytic cell at a ratio of 1:4700, and the circulation flow rate was set to 1.4 L / min. At a current density of 26 A / dm 2 Under the above conditions, the electrodeposition time was 41s, and a high performance 4.5 micron electrolytic copper foil was obtained.

[0065] Comparative Example 2

[0066] (1) By weight, 12 parts of cerium nitrate, 2850 parts of sulfur-containing brightener (sodium dimethylformamide sulfonate), 3450 parts of leveling agent (ethylene thiourea), 24 parts of wetting agent (hydroxyethyl cellulose), and 438,000 parts of deionized water were mixed.

[0067] (2) Prepare electrolyte, parameters are: electrolyte Cu 2+ concentration 86g / L, H2SO4 concentration 105g / L, Cl- Concentration 32g / L, temperature 58℃, circulation flow rate 42L / min.

[0068] (3) The additive and electrolyte are fully mixed in the electrolytic cell at a ratio of 1:4700, and the circulation flow rate is set to 1.4L / min and 28A / dm 2 The high performance 4.5 micron electrolytic copper foil is obtained by electroplating at a current density of 40 seconds.

[0069] Comparative Example 3

[0070] (1) By weight, 64 parts of polyacrylamide, 2810 parts of sulfur-containing brightener (sodium 3-mercapto-1-propanesulfonate), 3380 parts of leveling agent (collagen), 21 parts of wetting agent (hydroxymethyl cellulose), and 432,000 parts of deionized water were mixed.

[0071] (2) Electrolyte Cu 2+ Concentration 85g / L, H2SO4 concentration 102g / L, Cl - Concentration 28g / L, temperature 52℃, circulation flow rate 38L / min.

[0072] (3) After the additive and electrolyte are fully mixed in the electrolytic cell at a ratio of 1:4600, 24A / dm 2 Under the current density condition, the electrodeposition was carried out for 42 seconds to obtain the high performance 4.5 micron electrolytic copper foil.

[0073] Comparative Example 4

[0074] (1) By weight, 10 parts of cerium nitrate, 58 parts of polyacrylamide, 2820 parts of sulfur-containing brightener (sodium polydisulfide propane sulfonate), 3400 parts of leveling agent (ethylene thiourea and collagen mixed in a ratio of 2:1), 22 parts of wetting agent (hydroxyethyl cellulose and hydroxymethyl cellulose mixed in a ratio of 1:1), and 433,000 parts of deionized water were mixed uniformly.

[0075] (2) Prepare electrolyte with the following parameters: Cu 2+ Concentration 90g / L, H2SO4 concentration 96g / L, Cl - Concentration 26g / L, electrolyte temperature 53℃, circulation flow rate 35L / min.

[0076] (3) After the above additives and electrolyte are fully mixed in the electrolytic cell at a ratio of 1:4650, the circulation flow rate is set to 1.3L / min, and the current density is 25A / dm 2 Under the above conditions, the electrodeposition time was 42s, and a high performance 4.5 micron electrolytic copper foil was obtained.

[0077] The copper foil samples obtained in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 4 were subjected to the following performance tests:

[0078] (1) Tensile strength test

[0079] Test equipment: Microcomputer-controlled electronic universal testing machine.

[0080] Sample preparation: Cut a long strip sample with a width of 10 mm and a length of not less than 150 mm from the prepared 4.5-micron copper foil in the longitudinal direction, ensuring that the edges of the sample are neat and free of burrs.

[0081] Test process: Install the sample in the upper and lower clamps of the material testing machine, so that the axis of the sample coincides with the loading axis of the testing machine, and adjust the distance between the clamps so that the sample is in a naturally straight state without bending or twisting. Set the tensile speed of the testing machine to 5mm / min, start the testing machine to start the tensile test, and record the force-displacement curve of the sample from the beginning of loading to the fracture process.

[0082] Data processing: According to the force-displacement curve, the maximum tensile force F (unit: N) when the sample breaks is determined, and the tensile strength σ (unit: MPa) is calculated according to the formula σ = F / (A0), where A0 is the original cross-sectional area of ​​the sample (unit: mm 2 ), A0 = width × thickness, the width is 10 mm, the thickness is 4.5 microns, the thickness unit needs to be converted to mm (4.5 × 10 -3 For each embodiment and comparative example, at least 5 specimens were tested, and the average value was taken as the final tensile strength result. At the same time, the standard deviation was calculated to evaluate the dispersion of the data.

[0083] (2) Elongation test

[0084] Test equipment: Shared with the tensile strength test is a microcomputer-controlled electronic universal testing machine.

[0085] Sample preparation: Use the same specimens as for the tensile strength test.

[0086] Test process: While conducting the tensile strength test, the material testing machine automatically records the displacement changes during the tensile process of the sample. When the sample breaks, stop the test and record the gauge elongation ΔL (unit: mm) of the sample at this time. The gauge length can be marked on the sample by dotting or drawing, and the gauge length L0 is set to 50mm.

[0087] Data processing: The elongation δ is calculated according to the formula δ=(ΔL / L0)×100%. Similarly, at least 5 samples are tested for each embodiment and comparative example, and the average value and standard deviation are calculated as the final elongation result and the evaluation of the degree of data dispersion.

[0088] (3) Surface roughness test

[0089] Testing equipment: A portable surface roughness tester is used.

[0090] Sample preparation: Carefully cut a square sample of 10mm×10mm from the electrolytic copper foil, ensuring that the edges of the sample are neat and free of burrs, curling and other defects to avoid affecting the measurement results. Use a clean soft cloth dipped in an appropriate amount of anhydrous ethanol to gently wipe the surface of the sample to remove impurities such as oil, dust, fingerprints, etc. that may be contaminated on the surface, and then dry the sample naturally or blow it dry with clean compressed air to ensure that the surface is dry and clean to avoid foreign particles from damaging the stylus or interfering with the measurement results during the measurement process.

[0091] Test process: ① Place the roughness meter steadily on the test bench, turn on the power and preheat for 5-10 minutes to make the instrument reach a stable working state; ② Select appropriate roughness evaluation parameters. This test mainly focuses on the arithmetic mean roughness Ra and the maximum profile peak height Rz. According to the operating instructions of the roughness meter, set the corresponding measurement parameters, such as sampling length, evaluation length, etc. For 4.5 micron electrolytic copper foil, the sampling length is set to 0.8mm and the evaluation length is set to 4.0mm; ③ Fix the sample on the workbench of the roughness meter to ensure that the sample surface is horizontal and stable to avoid movement during the measurement process. Adjust the probe position of the roughness meter so that the probe is perpendicular to the sample surface and gently touches the sample surface. Be careful not to apply excessive pressure to avoid scratching the sample surface or affecting the measurement accuracy; ④ Start the measurement program of the roughness meter. The probe will move slowly on the sample surface according to the set measurement path to collect surface profile data. During the measurement process, keep the test environment quiet and stable to avoid external vibration from affecting the measurement results. Each sample shall be measured multiple times (at least 5 times) at different positions, and the measurement positions shall be evenly distributed on the sample surface.

[0092] Data processing: After the measurement is completed, the roughness meter will automatically display the Ra and Rz values ​​of each measurement. Record the parameter values ​​of each measurement position, eliminate abnormal values ​​(such as data that obviously deviates from other measurement values ​​due to local defects on the sample surface or accidental errors of the instrument during the measurement process), and calculate the average value as the surface roughness measurement result of the sample.

[0093] (4) Pinhole density test

[0094] Lay the sample flat on the light box, turn on the test light in the light box, turn off the lights in the pinhole test room, and the inspector visually observes whether there are any light-transmitting spots. If any light-transmitting spots are found, mark them, cut the marked samples and place them under a microscope at 100 times magnification for aperture size detection.

[0095] For each embodiment and comparative example, the arithmetic mean of the tensile strength, elongation and surface roughness test results of each sample was calculated as the final test result, and the standard deviation was calculated to evaluate the degree of discreteness of the data, so as to more accurately determine the effects of different additive formulations on the physical properties of the electrolytic copper foil.

[0096] The measured results are as follows Figure 1-3 As shown in Table 1 below:

[0097] Table 1 Test results

[0098]

[0099]

[0100] Note: 4.5μm copper foil: thickness tolerance (0, +2)μm, surface density (40.5±1.5)g / m 2 , tensile strength ≥ 300MPa, elongation ≥ 4%, smooth surface roughness Ra ≤ 0.43μm, rough surface roughness Rz ≤ 3.0μm, no pinholes

[0101] Results Analysis

[0102] 1. Tensile strength

[0103] In Examples 1 to 4, the average tensile strength is in the range of 436-446 MPa, and the standard deviation is between 0.8 and 3.3. The lower standard deviation indicates that the data dispersion is small and the repeatability is good, which strongly indicates that under certain conditions, the additive formula of the present invention can enable the 4.5 micron electrolytic copper foil to stably obtain a higher tensile strength, reaching a medium tensile strength level of 400-500 MPa.

[0104] Comparative Example 1 does not add cerium-polyacrylamide composite microspheres, and only uses a combination of sulfur-containing brightener, leveling agent and wetting agent. Its average tensile strength is only 174±1.1MPa, which is significantly lower than that of the embodiment. This clearly shows that cerium-polyacrylamide composite microspheres play an indispensable and key role in improving the tensile strength of copper foil. Comparative Example 2 adds cerium nitrate alone, and the tensile strength is 289±0.7MPa, which is higher than Comparative Example 1, but still significantly lower than the embodiment. It can be seen that compared with cerium ions alone, when present in the form of composite microspheres, the cerium element can more effectively play its role in improving tensile strength. Comparative Example 3 only adds polyacrylamide, and the tensile strength is 227±1.3MPa, which is also lower than the embodiment. This fully demonstrates that only when cerium and polyacrylamide work together can a more significant improvement in the tensile strength of copper foil be achieved. In comparative example 4, cerium nitrate and polyacrylamide were added simultaneously but composite microspheres were not formed, and the tensile strength was 307±3.0 MPa, which further strongly demonstrated the importance and unique advantages of the preparation method of the composite microspheres in the present invention and the synergistic effect between the components in improving the tensile strength of copper foil.

[0105] 2. Elongation

[0106] The average elongation values ​​of Examples 1 to 4 are distributed in the range of 7.85-8.36%, and the standard deviation is in the range of 0.03-0.06. The small standard deviation reflects that the elongation data has a high degree of stability. Among them, the elongation of Example 4 is as high as 8.36±0.03%, which fully highlights the excellent performance of the additive formula of the present invention in effectively improving the elongation of copper foil.

[0107] The elongation of comparative example 1 is 4.12±0.07%, and that of comparative example 3 is 4.55±0.11%, both of which are much lower than those of the embodiments. This once again proves that the cerium-polyacrylamide composite microspheres play a crucial and decisive role in improving the elongation of the material. The elongation of comparative example 2 is 5.61±0.10%, and that of comparative example 4 is 6.29±0.05%. Although the elongation of these two comparative examples is higher than that of some comparative examples, it is still significantly lower than that of the embodiments. This further strongly emphasizes the outstanding advantages of the overall formula and preparation method of the composite microspheres of the present invention in significantly improving the elongation of copper foil.

[0108] 3. Surface roughness

[0109] The smooth surface roughness Ra of Examples 1 to 4 is between 0.31-0.32 μm, and the matte surface roughness Rz is within the range of 1.75-2.05 μm, and the data fluctuations of each Example are small. This fully demonstrates that the additive formula of the present invention can effectively and accurately control the surface roughness of the copper foil, thereby ensuring that the copper foil has good surface quality.

[0110] The roughness of the smooth surface of all comparative examples is similar to that of the embodiments, because the roughness of the smooth surface of the copper foil mainly depends on the smoothness of the cathode plate. The roughness of the matte surface is greatly affected by the additive ingredients, which is fully reflected in the above comparative examples and embodiments. For example, the roughness Rz of the matte surface of comparative example 1, which only adds sulfur-containing brightener, leveling agent, and wetting agent, is as high as 3.17±0.08μm, which is much higher than that of the embodiments, indicating that the lack of cerium-polyacrylamide composite microspheres will cause the roughness of the matte surface of the copper foil to deteriorate significantly, thereby affecting the overall surface quality of the copper foil. The roughness of the matte surface of comparative examples 2 to 4 is slightly worse than that of the embodiments, indicating that the use of cerium ions and polyacrylamide alone or in combination has a certain improvement effect on the surface quality of the copper foil, which is consistent with the results of previous and existing studies. However, in terms of the index of surface roughness, the gap between the comparative examples and the embodiments is relatively small compared with the tensile strength and elongation.

[0111] 4. Pinhole situation

[0112] No pinholes were found in Examples 1 to 4, which indicates that the cerium-polyacrylamide composite microspheres and the additive formula in the present invention play an active and effective role in reducing the pinhole defects of copper foil, and help to significantly improve the quality of copper foil.

[0113] The number of pinholes in Comparative Example 1 is greater than 10, and the number of pinholes in Comparative Example 3 is greater than 10, which is in sharp contrast to the examples, and once again confirms the importance and effectiveness of the cerium-polyacrylamide composite microspheres and additive formula in reducing pinhole defects and improving the quality of copper foil. The number of pinholes in Comparative Example 2 is ≤5, and the number of pinholes in Comparative Example 4 is ≤5, which shows that in terms of reducing pinholes, adding cerium or polyacrylamide alone can also play a role to a certain extent, but the additive formula containing composite microspheres provided by the present invention is more effective in reducing pinholes, and can better meet the needs of high-quality copper foil production.

[0114] in conclusion

[0115] The high-performance 4.5-micron electrolytic copper foil additive formula and its application method proposed by the present invention are practical and effective. Through a comprehensive comparative analysis of the embodiments and comparative examples, it can be seen that the additive formula containing cerium-polyacrylamide composite microspheres has outstanding advantages in significantly improving the tensile strength and elongation of 4.5-micron electrolytic copper foil and effectively improving the surface quality (including reducing surface roughness and reducing pinhole defects).

[0116] The unique preparation method of cerium-polyacrylamide composite microspheres and the synergistic effect between the components are crucial to improving the tensile strength and elongation of copper foil. The excellent effect brought by the composite microspheres cannot be achieved by adding cerium salt or polyacrylamide alone. Only by successfully forming composite microspheres through the in-situ polymerization method provided by the present invention and reasonably proportioning with other additives (such as sulfur-containing brighteners, leveling agents, wetting agents) can a 4.5-micron electrolytic copper foil with high performance be prepared, thereby meeting the reliability requirements during production and use, and having broad application prospects and significant practical value in the field of electrolytic copper foil.

[0117] The above examples further illustrate the feasibility and effectiveness of the additive of the present invention and its preparation method in producing high-performance 4.5 micron electrolytic copper foil, and can obtain high-performance copper foil with good surface quality, tensile strength of 400-500MPa and elongation of more than 7%.

[0118] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.

Claims

1. A high-performance 4.5 micron electrolytic copper foil additive, characterized in that: By weight, It includes the following components: 32-65 parts of cerium-polyacrylamide composite microspheres Sulfur-containing brightener 2800-2870 parts Leveling agent 3360~3500 parts Wetting agent 20-26 parts 430,000 to 440,000 parts of deionized water.

2. A high performance 4.5 micron electrolytic copper foil additive according to claim 1, characterized in that: The preparation method of the cerium-polyacrylamide composite microspheres is as follows: (S1) Raw material preparation: select a cerium salt and dissolve it in deionized water to prepare a cerium ion solution with a concentration of 0.1-1 mol / L; weigh acrylamide monomer and dry it in a vacuum drying oven; and prepare an initiator, a crosslinking agent and a surfactant; (S2) Monomer dissolution: slowly adding the dried acrylamide monomer to the cerium ion solution to make the concentration of the acrylamide monomer be 1-5 mol / L, and stirring until the acrylamide monomer is completely dissolved in the cerium ion solution to form a mixed solution; (S3) Adding auxiliary agents: adding an initiator, a cross-linking agent and a surfactant to the mixed solution in sequence, and stirring to disperse them uniformly; (S4) In-situ polymerization: the prepared reaction system is transferred to a reactor, the temperature is raised to 50-70° C., and the reaction is continuously stirred at a rotation speed of 200-400 rpm for 3-6 hours; (S5) post-processing the product to obtain the cerium-polyacrylamide composite microspheres.

3. A high performance 4.5 micron electrolytic copper foil additive according to claim 2, characterized in that: In step (S1), the acrylamide monomer is dried in a vacuum drying oven at 40-50° C. for 2-3 hours.

4. A high performance 4.5 micron electrolytic copper foil additive according to claim 2, characterized in that: The cerium salt is one or more of cerium nitrate, ammonium cerium nitrate, cerium sulfate and cerium chloride; the initiator is ammonium persulfate or potassium persulfate; the crosslinking agent is N,N-methylenebisacrylamide; and the surfactant is sodium dodecyl sulfate or sodium dodecylbenzene sulfonate.

5. A high performance 4.5 micron electrolytic copper foil additive according to claim 2, characterized in that: In step (S3), the amount of the initiator added is 0.5%-2% of the mass of the acrylamide monomer, the amount of the crosslinking agent added is 0.05%-0.5% of the mass of the acrylamide monomer, and the amount of the surfactant added is 2%-4% of the total mass of the reaction system.

6. A high performance 4.5 micron electrolytic copper foil additive according to claim 2, characterized in that: The specific operation of step (S5) is as follows: after the reaction is completed, the product in the reactor is cooled to room temperature, and then the product is transferred to a centrifuge tube, and centrifuged at a speed of 3000-5000rpm for 10-20 minutes in a centrifuge to allow the microspheres to settle at the bottom of the centrifuge tube, and the supernatant is poured out to collect the microspheres; then, the collected microspheres are washed with deionized water, and the number of washing times is 3-5 times; each time the microspheres are washed, the microspheres are redispersed in deionized water, and then centrifuged at a speed of 3000-5000rpm for 10-20 minutes in a centrifuge, and the supernatant is poured out to remove unreacted substances and impurities; finally, the washed microspheres are transferred to a vacuum drying oven, and dried for 12-24 hours at a temperature of 50-60°C and a vacuum degree of 0.05-0.1MPa to obtain the cerium-polyacrylamide composite microspheres.

7. A high performance 4.5 micron electrolytic copper foil additive according to claim 1, characterized in that: The sulfur-containing brightener is at least one of sodium alcoholthiopropane sulfonate, sodium polydisulfide propane sulfonate, sodium dimethylformamide sulfonate, and sodium 3-mercapto-1-propane sulfonate.

8. The high performance 4.5 micron electrolytic copper foil additive according to claim 1, characterized in that: The wetting agent is at least one of polyethylene glycol, hydroxyethyl cellulose and hydroxymethyl cellulose.

9. The high performance 4.5 micron electrolytic copper foil additive according to claim 1, characterized in that: The leveling agent is at least one of tetrahydrothiazolidinethione, ethylenethiourea, gelatin and collagen.

10. Use of the additive according to any one of claims 1 to 9 in electrodeposition of 4.5 micron electrolytic copper foil.

Citation Information

Patent Citations

  • 4.5 micrometer electrolytic copper foil for lithium ion battery, preparation method and additive

    CN110644021A

  • Additive for improving 4.5-micron lithium ion electrolytic copper foil pinholes

    CN112760682A

  • Preparation method of 3-micron electrolytic copper foil additive, product and application of 3-micron electrolytic copper foil additive

    CN113652718A

Cited By

  • Ultrasonic vibration assisted large-width copper plate strip continuous extrusion short-process technology

    CN121017293A